Possible involvement of the oxLDL/LOX-1 system in the pathogenesis and progression of human intervertebral disc degeneration or herniation - Xinhua Li (Nature Portfolio, 2017)
Abstract Epidemiological studies have concluded that hyperlipidemia and atherosclerosis were related to intervertebral disc degeneration (IVDD). The presence of oxidized low density lipoprotein (ox-LDL) and the expression of lectin-like oxidized low density lipoprotein receptor 1 (LOX-1) have not been explored in this tissue. In this study, we investigated the presence of ox-LDL and the expression of its receptor LOX-1 in non-degenerated, degenerated or herniated human intervertebral discs (IVDs). The expression of LOX-1 and matrix metalloproteinase 3 (MMP3) were studied after incubating nucleus pulposus cells (NPCs) with ox-LDL. The presence of ox-LDL and LOX-1 was positively related with the extent of IVDD in nucleus pulposus (NP), end-plate cartilage and outer annulus fibrous, but not with the extent of degeneration of inter annulus fibrous. Ox-LDL significantly reduced the viability of human NPCs in a dose and time-dependent manner, and increased the expression of MMP3 induced by LOX-1. Pretreatment with anti-human LOX-1 monoclonal antibody reversed these effects. Ox-LDL, principally mediated by LOX-1, enhanced MMP3 production in NPCs through the NF-κB signaling pathway. In conclusion, increased accumulation of ox-LDL and LOX-1 in IVDs indicates a specific role of the receptor-ligand interaction in degeneration or herniation of IVDs.